Implementation of online learning to improve understanding concept and exhaustiveness of learning outcomes on science lesson - W Trisnawaty (Pascasarjana Universitas Pendidikan Indonesia, 2018)
The aims of this research were improving the understanding of concepts and exhaustiveness of student learning outcomes on science lesson using online learning. It was a classroom action research that using Kemmis and Mc Taggart model. Subject of this research were student of mathematics education program on even semester. Data collection techniques include tests, observations, and questionnaires. It was analyzed descriptively qualitative. From this research founded that student’s understanding concept on the first cycle is 70.1%, and the second cycle is 91.5%, the average of student learning outcomes in cycle I is 65 and the second cycle is 83.5. Based on those findings, it could be concluded that the implementation of online learning can increase understanding of concepts and exhaustiveness of student learning outcomes on science lesson.